Effect of weather conditions on tree stability in Singapore - Li, Yangyang (Nanyang Technological University, 2020)
This work presents an integrated approach to modelling the effect of weather conditions on tree stability, including wind, rainfall, temperature, humidity and solar radiation. This approach includes computation of the drag force in computational fluid dynamics (CFD) analyses and evaluation of the behaviour of the trunk-root-soil system under the wind drags applied in deformation analyses. In the deformation analyses, the effects of weather conditions on soil strength and stiffness were incorporated. Soil strength and stiffness are related to the pore-water pressure of soil, which are affected by rainwater infiltration and evapotranspiration related to weather conditions. The drag coefficients of one mature Khaya senegalensis tree and one Eugenia grandis tree in Singapore were computed from both CFD analyses and field measurements. The CFD analyses took advantage of the laser scanning approach to generate tree geometries and calculate three-dimensional (3D) leaf area density (LAD) distribution. Multiple porous domains were used to represent the canopy. Within each porous domain, the source and sink terms, as a function of LAD, were used to simulate the turbulent effects of leaves. CFD analyses were performed using ANSYS 17.2 (i.e. the most updated version in 2016). In addition, drag coefficients were calculated from field measurements including wind speeds, tree deflections and the average elastic moduli of the trees. The drag coefficients from the CFD analyses and field measurements were then compared and possible reasons for the difference were discussed. The deflections of the Eugenia grandis tree under wind drag in Singapore during a 20-day monitoring period were analysed in 3D using ANSYS 19.1 (i.e. the most updated version in 2018). The soil strength and modulus were dependent on the pore-water pressure head of soil. To obtain the pore-water pressure head distribution of soil, one-dimensional (1D) analyses were performed using VADOSE modelling in GeoStudio 2012 based on the weather conditions recorded from the field instrumentations during the 20 days. Using wind drag calculated from the CFD analyses, the lean of the Eugenia Grandis tree during the study period was computed by incorporating changes in soil stiffness and soil strength due to changes in pore-water pressure head of the soil. It was found that the estimated tree lean increased by 16.5% when the change in soil strength and soil modulus as effects of weather conditions were considered, as compared to tree lean calculations without consideration of changes in soil and with the assumption of a constant soil modulus of 20 MPa. These findings highlight the need to consider the effect of weather conditions on soil strength and modulus when analysing tree deflections.